1992
DOI: 10.1161/01.cir.85.5.1751
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of skeletal muscle in chronic heart failure.

Abstract: Elisabeth Funke, BS; and Hanj6rg Just, MD Background. The present study was designed to define the prevalence and characteristics of skeletal muscle alterations in patients with chronic heart failure (CHF) and their relation to exercise capacity.Methods and Results. The ultrastructure of skeletal muscle was analyzed by ultrastructural morphometry in 57 patients with CHF and 18 healthy controls. The volume density of mitochondria (Vvm) and the surface density (Svmc) of mitochondrial cristae were evaluated as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
449
5
28

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 692 publications
(499 citation statements)
references
References 53 publications
17
449
5
28
Order By: Relevance
“…Nevertheless, this long-term decline in exercise tolerance following the procedure may also be related to the disease progression (17) or to the reduced capacity to increase the cardiac output (Q) in response to exercise secondary to the Fontantype circulation, thus limiting the oxygen transport to the periphery (22,23). Slower oxygen uptake kinetics, ie, the precise integration of the cardiorespiratory system required to transport the oxygen from the atmosphere through active muscles to achieve oxidative phosphorylation (24), is well documented in patients with coronary artery disease, cyanotic congenital heart disease or heart failure (25)(26)(27)(28)(29)(30)(31). In patients who have had a Fontan procedure, slower oxygen uptake kinetics was observed compared with those of healthy individuals, suggesting alterations in the central component (oxygen transport) and/or in the peripheral component (oxygen utilization) during exercise (32).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Nevertheless, this long-term decline in exercise tolerance following the procedure may also be related to the disease progression (17) or to the reduced capacity to increase the cardiac output (Q) in response to exercise secondary to the Fontantype circulation, thus limiting the oxygen transport to the periphery (22,23). Slower oxygen uptake kinetics, ie, the precise integration of the cardiorespiratory system required to transport the oxygen from the atmosphere through active muscles to achieve oxidative phosphorylation (24), is well documented in patients with coronary artery disease, cyanotic congenital heart disease or heart failure (25)(26)(27)(28)(29)(30)(31). In patients who have had a Fontan procedure, slower oxygen uptake kinetics was observed compared with those of healthy individuals, suggesting alterations in the central component (oxygen transport) and/or in the peripheral component (oxygen utilization) during exercise (32).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…For example, declines in immune function with age increase the risk of pulmonary viral and bacterial infections leading to pneumonia. Decreased physical activity will lead to deconditioning of cardiopulmonary function, general vascular tone, and the fitness of voluntary muscles that may impair the efficiency of peripheral vascular function (10,18,20,21). Thus, current reductions in the prevalence of chronic disability may affect the future prevalence of chronic disease and mortality risk in the United States elderly population.…”
mentioning
confidence: 99%
“…Although the results for quality of life were not different between the groups, it can be observed that in the present study day-to-day activities, represented by the 6MWT, CT and ST, were impaired for patients with HF+PVI. We believe that histological abnormalities in skeletal muscle of HF patients, such as muscle atrophy and reduced mitochondrial density, [21][22][23] may have impacted these patients' capacity for microvascular O 2 extraction. This in turn suggests that the patients with mixed disease suffer greater musculoskeletal compromise, leading to lower tolerance of exercise, as observed in the clinical tests.…”
Section: Discussionmentioning
confidence: 99%